Oxygen gradients can determine epigenetic asymmetry and cellular differentiation via differential regulation of Tet activity in embryonic stem cells. Issue 3 (24th November 2017) - Burr, Simon; Caldwell, Anna; Chong, Mei; Beretta, Matteo; Metcalf, Stephen; Hancock, Matthew; Arno, Matthew; Balu, Sucharitha; Kropf, Valeria Leon; Mistry, Rajesh K; Shah, Ajay M; Mann, Giovanni E; et al.
Abstract: Graded levels of molecular oxygen (O2 ) exist within developing mammalian embryos and can differentially regulate cellular specification pathways. During differentiation, cells acquire distinct epigenetic landscapes, which determine their function, however the mechanisms which regulate this are poorly understood. The demethylation of 5-methylcytosine (5mC) is achieved via successive oxidation reactions catalysed by the Ten-Eleven-Translocation (Tet) enzymes, yielding the 5-hydroxymethylcytosine (5hmC) intermediate. These require O2 as a co-factor, and hence may link epigenetic processes directly to O2 gradients during development. We demonstrate that the activities of Tet enzymes display distinct patterns of [O2 ]-dependency, and that Tet1 activity, specifically, is subject to differential regulation within a range of O2 which is physiologically relevant in embryogenesis. Further, differentiating embryonic stem cells displayed a transient burst of 5hmC, which was both dependent upon Tet1 and inhibited by low (1%) [O2 ]. A GC-rich promoter region within the Tet3 locus was identified as a significant target of this 5mC-hydroxylation. Further, this region was shown to associate with Tet1, and display the histone epigenetic marks, H3K4me3 and H3K27me3, which are characteristic of a bivalent, developmentally 'poised' promoter. We conclude that Tet1 activity, determined by [O2 ] may play a critical role in regulating cellular differentiation and fate in embryogenesis.